IMPROVING KNOWLEDGE MANAGEMENT PROCESS USING BIM IN INDONESIAN STATE-OWNED CONSTRUCTION ENTERPRISES - Fitra, Singgih; Negara , Kartika Puspa; Wijatmiko , Indradi (POLITEKNIK NEGERI JAKARTA, 2024)
In today's digital era 4.0, the synergy between the construction industry and information technology is inevitable. Knowledge management plays a critical role in the success of construction companies, enabling them to effectively capture, store, share, and utilize valuable information and expertise. In recent years, Building Information Modeling (BIM) has emerged as a powerful tool that improves knowledge management in the construction industry. This article focuses on implementing BIM in Indonesian state-owned construction companies and how it can improve knowledge management, leading to better project outcomes, efficiency, and competitiveness. BIM-based Knowledge Management (KM) systems can capture, store, and disseminate knowledge to manage facilities through their life cycle. To describe in this study first identified from a literature review how BIM can facilitate improved knowledge management in construction projects. Second, a questionnaire survey of respondents of State Owned Construction Enterprises with ISO 1960 BIM in Indonesia will be further analyzed using a quantitative SEM-PLS analysis to determine the KM types that can be leveled using BIM. The variables used in this study are BIM implementation on KM, processes, effectiveness, and barriers to knowledge management. The results of this study show that BIM performance positively affects KM process improvement, KM effectiveness, and KM obstacle alleviation.